Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Let $(X_i)_{i\ge 1}$ be i.i.d random variables, and let $(e_i)_{i \ge 1}$ be i.i.d random variables independent from the $(X_i)$. Assume $0\lt E(X_i^2) \lt +\infty$ and let $m = E(X_i), \sigma^2 = E(X_i^2)$. Assume as well that $e_1$ can only take values 1 and 2 with $P(e_1 = 1) = p, P(e_1 = 2) = 1-p$. Finally, define the product $M_n =X_1^{e_1}...X_n^{e_n}$. For what value of $p$ is $(M_n)$ a martingale?

Ok so for $(M_n)$ to be a martingale $E(M_{n+1}|X_1,...,X_n)= M_nE(X_{n+1}^{e_{n+1}})= M_n$

I think we have to use the limiting properties regarding the value of $p$ i.e. show that if $p<1/2$ then $M_n$ approaches $X_1^{2}...X_n^{2} $ or $M_n = X_1...X_n$ if $p>1/2$ but im not too sure.

Any help would be appreciated,


share|cite|improve this question
up vote 2 down vote accepted

You are nearly there. $M_n E(X_{n+1}^{e_{n+1}})=M_n\implies E(X_{n+1}^{e_{n+1}})=1$.

$$E(X_{n+1}^{e_{n+1}})=pE(X_{n+1})+(1-p)E(X_{n+1}^2)\\ =pm+(1-p)\sigma^2=1$$

Express $p$ in terms of $m$ and $\sigma^2$ and you are done!

share|cite|improve this answer

It's much more simpler, you just stopped on a halfway. You've correctly mentioned that $$ \mathsf E[M_{n+1}|X_1,\dots,X_n] = M_n\cdot\mathsf E[X_{n+1}^{e_{n+1}}] $$ thus you have to have $\mathsf E[X_{n+1}^{e_{n+1}}] = 1$ for $M_n$ to be a martingale. You have: $$ \mathsf E[X_{n+1}^{e_{n+1}}] = p\cdot\mathsf E X_{n+1}+(1-p)\cdot\mathsf E X_{n+1}^2 = p(m-\sigma^2)+\sigma^2 $$ and thus $$ p = \frac{1-\sigma^2}{m-\sigma^2}. $$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.